Exploring the Role of Mutual Trust in Human-Robot Interactions - Triglia, Laura (2024 12th International Conference on Affective Computing and Intelligent Interaction Workshops and Demos (ACIIW), 2024)
This research seeks to construct a comprehensive model of mutual trust in human-robot interactions, an under-explored yet critical aspect of HRI. My PhD work aims to determine if mutual trust transcends the robot's physical form and enhances human engagement. Additionally, I will investigate mutual trust within group dynamics to assess its influence on collective perceptions and interactions. The initial phase focuses on developing a robust framework for studying mutual trust, setting the stage for future exploration of its profound impact on human-robot relationships.